Experimental correlation for flow-boiling heat transfer in a micro-gap evaporator with internal micro-fins - Ahmed, Shugata; Ismail, Ahmad Faris; Sulaeman, Erwin; Hasan, Muhammad Hasibul (Penerbit Akademia Baru, 2019)
Micro-gap evaporators are prospective candidates for cooling of micro-electronic devices. Heat transfer with phase change in a micro-gap heat sink is efficient for high heat flux applications. Micro-fins induce turbulence escalating two-phase heat transfer rate in the micro-gap evaporator. However, no correlation has been developed so far for fin-induced pseudo-turbulence and heat transfer rate in micro-gap heat sink. The scope of this paper is to develop a correlation for dimensionless heat transfer rate in a micro-finned micro-gap heat sink for refrigerant 134a. The correlation signifies the effect of evaporation rate on thermal resistance of the heat sink. For this purpose, a micro-gap evaporator was fabricated with a gap height adjusted to accommodate 48 rectangular shaped micro-fins. A heater at the bottom of the heat sink provides variable heat flux. The evaporator is installed in a test section along with a heat pump in the outer circuit. The frequency of the compressor is varied using a variable frequency drive. A pre-heater is used to vary inlet temperature of refrigerant. In the developed correlation, dimensionless heat flux is function of calculated vapor Reynolds number and Biot number. Results calculated from the correlation show maximum 2.7% error in comparison to actual results